Language practice in the multilingual workplace: A Confucius Institute in Macau - Yang (Frank), Gong; Xuesong (Andy), Gao; Citing, Li; Lian, Xue (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This article reports on an ethnographic study that investigated language practice in a multilingual workplace, a Confucius Institute in Macau. In the study we collected multiple data from five staff members through participatory observations, open-ended interviews, and field notes, to examine their language practice in the Institute. The analysis revealed that multiple languages were chosen to fulfill different purposes on different occasions. Specifically, Putonghua served as the working language of the Institute, English emerged as an auxiliary language along with Putonghua, and Cantonese was used as a group language for native-Cantonese speaker staff. This study also identified that the staff members adopted multilingualism (flexibly using different languages) and English as a lingua franca for communicating with learners outside the classroom, as important strategies for dealing with tasks in encounters with language diversity, divergence between spoken communication and written communication, and lack of multilingual competence. These findings suggest that the stakeholders in Confucius Institutes need to pay more attention to the language practice in these multilingual settings, and provide resources and support to enhance the staff’s bilingual/multilingual communication competence